Synergy of advanced processing techniques using copernicus sar and optical satellite imagery to detect ground displacements : the case studies of Pyrgos and Parekklisia villages in Cyprus - Tzouvaras, Marios; Alatza, Stavroula; Prodromou, Maria; Theocharidis, Christos; Fotiou, Kyriaki; Argyriou, Athanasios V.; Loupasakis, Constantinos; Apostolakis, Alexis; Pittaki, Zampella; Kaskara, Mariza; Kontoes, Charalampos; Hadjimitsis, Diofantos G. (My University, 2023)
Cyprus has a long history of destructive tectonic activity and related geohazards. This is mainly due to its location on the Mediterranean fault zone and the interaction of the Eurasian and African plates. To study the occurrence of land displacements on a national scale, various space-based monitoring techniques exploiting the Copernicus program’s datasets were studied using Sentinel-1 and Sentinel-2 satellite images for the period of 2016-2021. More specifically, differential spectral indices were calculated by subtracting the reference 2016 Sentinel-2 image from an image for every year until 2021, and a parallelised version of Persistent Scatterer Interferometry (PSI) was conducted using a time series of Sentinel-1 data over the same period, to identify ground displacements over time. The PSI analysis in the area around Pyrgos and Parekklisia villages, detected Line-of-Sight (LoS) uplift phenomena of a maximum rate of 8 mm/y, in ascending and descending Sentinel-1 satellite passes. Similarly, deformation was identified from optical image processing. The integration of both techniques provided qualitative and quantitative information about ground deformation events in both areas, showcasing a complementarity of results obtained, with PSI detecting displacements in urban/built-up areas, and multispectral change detection in rural environment. In terms of correlation, the two techniques showed a fit of 31.34% in ascending and 26% in descending pass, providing additional information on the size of affected areas. This synergistic approach facilitates the systematic monitoring of areas of interest, providing significant and timely information to decision-makers, to take actions and adopt protective measures when and where it is required.
Keywords: Disaster Risk Reduction; Geohazards; Google Earth Engine; Observatory; Decision support tool